2005
DOI: 10.1007/s10397-005-0131-7
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of dysfunctional uterine bleeding with the Mirena IUS: a survival analysis

Abstract: A questionnaire was sent to 124 women with dysfunctional uterine bleeding (DUB) who had been treated with the Mirena IUS. Prior to treatment, the women had received advice about the side effects of the Mirena IUS. There was a 71% response rate of which 21% had the Mirena IUS removed prematurely. The main reasons for removal were pelvic pain and irregular vaginal bleeding. The projected Kaplan-Meier survival rate for the device over the 5-year therapeutic lifetime was 55%. The amenorrhoea rate was 38% and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Studies reported its maximum efficacy 1 year after insertion with a significant reduction of menstrual blood loss upto 97%. 17,20 In Hurskainen et al's trial it was found to be cost effective than hysterectomy. 21…”
Section: Levonorgestrel-releasing Intrauterine Devicementioning
confidence: 99%
“…Studies reported its maximum efficacy 1 year after insertion with a significant reduction of menstrual blood loss upto 97%. 17,20 In Hurskainen et al's trial it was found to be cost effective than hysterectomy. 21…”
Section: Levonorgestrel-releasing Intrauterine Devicementioning
confidence: 99%
“…Studies report reduction of blood loss in menstrual cycles up to 97%, with its maximum efficacy 1 year after insertion [24,[28][29][30][31]. The majority of women with Mirena® bleed only for 1 day or experience just spotting during their period, while 15% of them become amenorrheic [31].…”
Section: Levonorgestrel-releasing Intrauterine Devicementioning
confidence: 99%
“…Ewies does not cite other studies that have shown higher continuation rates in the treatment of HMB [1][2][3][4]. We suggest that it would have been appropriate to compare the continuation rates of the LNG-IUS with a comparator treatment.…”
mentioning
confidence: 92%